The University as an Ecological Territory of the Incoming Student: virtual inclusion during the COVID-19 pandemic - Bueno, Maria Angélica de Moura; Pinto, Lauren Machado; Cesar, Maria Rita Assis; Gomes, Júlio (Multi-Science Journal, 2022)
The article aims to present the ecological territory as an extension project with students entering a federal public university in the south of Brazil while performing virtual workshops during the COVID-19 pandemic. The realization of virtual workshops of the IN project focused on the incoming student (IN) and provided group meetings on themes of the university scope. Thus, we intend to present the experience of developing meetings in virtual workshops in everyday life, considering ecological territory as a daily life to be known and explored by students. The ecological universe gives the university a sense of relationship in an intersectoral and participative nexus in the dynamic spheres, which is vital to academic and personal development. This descriptive and qualitative study covers 32 meetings out of 437 virtual invitations sent, reaching the voluntary participation of 62 students enrolled in the IN Virtual Workshops. Through the content analysis method, we obtained qualitative results from the field diaries in the virtual workshops regarding the sense of belonging, vulnerability, distance education, and social support network. It concludes by excluding online alternatives of contact with incoming students as a public policy of inclusion and university permanence and identifying themselves as a way of welcoming and preventing mental health.